Dampak Pengembangan Sumber Daya Manusia, Budaya Organisasi Dan Perilaku Kerja Inovatif Terhadap Kinerja Pegawai Badan Perencanaan Pembangunan, Riset Dan Inovasi Daerah (Bapperida) Kabupaten Klaten - Anggorowati Dwi Saputro; Etty Indriani (STIE AUB Surakarta, 2026)
This study aims to examine the influence of human resource development and organizational culture on innovative work behavior and employee performance at the Regional Development Planning, Research, and Innovation Agency (Bapperida) of Klaten Regency. The study used primary data with a sample of 40 employees. Data analysis methods included validity, reliability, linearity, partial t-tests, simultaneous t-tests (F-tests), coefficient of determination (R²), and path analysis.The results showed that human resource development had a positive and significant effect on employee performance, while organizational culture had a negative but insignificant effect. Innovative work behavior had a positive and significant effect on employee performance. Furthermore, human resource development had a positive but insignificant effect on innovative work behavior, while organizational culture had a positive and significant effect on innovative work behavior.The determination test results showed a total R² value of 0.9225, indicating that employee performance can be explained by human resource development and organizational culture, with innovative work behavior as an intervening variable, at 92.25%. Path analysis shows that innovative work behavior does not act as an effective intervening variable in the relationship between HR development and employee performance, but acts as an effective intervening variable in the relationship between organizational culture and employee performance at the Regional Development Planning, Research, and Innovation Agency (Bapperida) of Klaten Regency.